COVID-19 Vaccination Policy: Quo Vadis Fulfillment of Citizen’s Right to Life - Fahmi Fairuzzaman; Deva Angger Rakasiwi; Galih Aprillia Wibowo; Imaniar Rinanda Ayuningtyas (Universitas Muhammadiyah Surakarta, 2021)
This article aimed to analyze the factors that influence the pros and cons of the community regarding the COVID-19 vaccine policy and discuss the formulation of the Indonesian Government's policy regarding the distribution of an effective vaccine to realize the right to life amid the COVID-19 pandemic. Furthermore, the methodology of this research is normative, in the hope that the research approach was carried out for researchers to obtain information from various aspects in order to find the issues to be addressed. Normative research uses legal materials obtained through scientific literature or the law. The results of the conclusion show that the factors influencing the pros and cons of the community regarding the fulfillment of the right to life through vaccine policies consisted of multicultural settings that affected the mindset and perspective of the community in perceiving the COVID-19 virus outbreak so that there were differences of opinion regarding government policies that echoed mass vaccines to aggravate the number of the positive cases. Besides, the government's consistency factor in the form of data disclosure regarding COVID-19 led the public to obtain inaccurate information from various sources, giving rise to diverse public opinions. The formulation of government policies related to the provision of effective vaccines to realize the right to life amid the COVID-19 pandemic was done through the 3S vaccine policy, namely before the vaccine, during the vaccine, and after the vaccine. These included campaigns of the main objectives of the COVID-19 vaccine, priority allocation of COVID-19 vaccinations, and efforts to supervise COVID-19 vaccinations.